PENGARUH KESEHATAN DAN KESELAMATAN KERJA (K3) TERHADAP KINERJA KARYAWAN DI PUSKESMAS MELONG ASIH - Muchammad Fahad Firdaus; Ahmad Abdul Goib; Ceria Febiana (Sekolah Tinggi Pariwisata Mataram, 2021)
This research aims to identify the influence of occupational safety and occupational health on employee’s performance at PUSKESMAS Melong Asih. The research data is obtained by giving questionnaires to 50 employees. The research findings indicate that both occupational safety and health have influence on employee’s performance with significance value of 0.002. In order to maintain the occupational safety and health, it is suggested that the employees must obey the regulations.